Proposta de um banco de dados biológicos para pesquisa do Mero (Epinephelus itajara) - Suzuki, Danielle Forbeci (2014)
The increase in data collect of biological and the lack of standardization in scientific research requires improved information management. The objective of this dissertation is to propose a model database for further analysis and centralization of information for brasilian scientists of mero. In the selection of attributes were used knowledge of the areas of biology and of informatics in a multidisciplinary approach. Was researched and was compiled a selection of attributes removed from from the specialized scientific literature national and international, and validated by the application of an interview with experts involved in research with the fish Mero (Grouper Itajara). At the end of the survey were selected attributes that grouped into tables were used in the creation of the database, it biological, ecological, geographical information collected from articles and with experts. With the creation of this database seeks to establish integration between all of the researchers involved in order to create a single query and storage base in real time information. It is noted that, with the standardization in the collection of data and information on this species, we can promote a better status of evaluation and management for the conservation of species.